2019
DOI: 10.1002/jcp.28810
|View full text |Cite
|
Sign up to set email alerts
|

STRIP2 silencing inhibits vascular smooth muscle cell proliferation and migration via P38–AKT–MMP‐2 signaling pathway

Abstract: STRIP2 (FAM40B) was reported to regulate tumor cell migration. Our study aims to discuss the effect of STRIP2 in mouse aortic smooth muscle cell (MOVAS) proliferation and migration processes, which contributes greatly to atherosclerosis formation. In MOVAS cells, STRIP2 depletion suppressed cell proliferation and migration, which were related to a remarkable decrease in matrix metalloproteinases-2 (MMP-2)/MMP-9 expression. Additionally, P38 mitogen-activated protein kinases and Protein kinase B (AKT) are inact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…However, a few articles reported that STRIP2 was involved in the modulation of the Akt/mTOR pathway. The deficiency of STRIP2 has been illustrated to restrain the proliferation and migration of vascular smooth muscle cells through affecting the Akt pathway . In line with the earlier reports, our article manifested that overexpression of STRIP2 promoted cell proliferation, which might be achieved by the activation of the Akt/mTOR pathway in LUAD cells.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, a few articles reported that STRIP2 was involved in the modulation of the Akt/mTOR pathway. The deficiency of STRIP2 has been illustrated to restrain the proliferation and migration of vascular smooth muscle cells through affecting the Akt pathway . In line with the earlier reports, our article manifested that overexpression of STRIP2 promoted cell proliferation, which might be achieved by the activation of the Akt/mTOR pathway in LUAD cells.…”
Section: Discussionsupporting
confidence: 89%
“…Increasingly, dysregulation of STRIPAK components is involved in various diseases including cancer [9]. Striatin-interacting protein 2 (STRIP2), as one member of the STRIPAK complex and also called Fam40b, took part in regulating tumor cell growth and migration [10,11]. According to the research by Madsen et al [11], STRIP2 ablation lessened cell migration of breast cancer cells.…”
mentioning
confidence: 99%
“…22 MMP-2 and -9 promote the development of atherosclerosis and are recognized as major factors in causing plaque destabilization. 23 The expression of MMP-2 and -9 were elevated in the ApoE −/− mice, while the present study data confirmed that both MMP-2 and -9 mRNA levels were normalized in response to TPPU treatment. Furthermore, the underlying molecular mechanism of TPPU on suppressing macrophages foam cell formation is mediated by reducing oxLDL internalization and elevating cholesterol efflux, rather than endogenous cholesterol synthesis.…”
Section: Discussionsupporting
confidence: 83%
“…57 MMPs also play a role in vascular remodelling by modulating the migration and proliferation of smooth muscle cells and endothelial cells and mediating the release of the smooth muscle cell mitogens and growth factors, increasing the risk of COPD pulmonary hypertension. [58][59][60][61] The endogenous inhibitors of MMPs are tissue inhibitors of metalloproteinases (TIMPs). TIMPs are a family of low-molecular-weight proteins with four known members.…”
Section: Copd Pathogenesismentioning
confidence: 99%